Sense of coherence mediates the effects of low work ability on mental distress during unemployment - Vastamäki, Jaana; Wolff, Hans-Georg; Paul, Karsten Ingmar; Moser, Klaus (Journal of Workplace Behavioral Health, 2014)
Previous research has found that work ability (as measured with the Work Ability Index) is related to mental health in employee samples and in the general population. This study extends this research to unemployed people. In addition, it tests whether the effect of impaired work ability on mental health can be explained by changes in sense of coherence. A longitudinal design with two measurement points was used with a sample (N = 98) of jobless individuals in Finland participating in labor market interventions. Consistent with expectations, impaired work ability predicted lower sense of coherence and more psychological distress, and the association between impaired work ability and distress was mediated by sense of coherence. The important role of impaired work ability for jobless individuals' sense of coherence and, consequently, mental health during unemployment is discussed.
Keywords: distress; sense of coherence; unemployment; WAI; work ability